Uganda : adjustment with growth 1987-94 - Sharer, Robert L. (IMF WashingtonUS, 1995)
Presents an overview of recent economic performance and considers the economy's performance with respect to growth saving and investment. Provides an analysis of Uganda's external adjustment efforts and, in particular, its move toward external viability and sustainable balance of payments position. Surveys fiscal adjustment over the period and the prospects for a sustainable fiscal position. Focuses on financial sector reform. Examines the economy from a regional perspective.